Pengembangan Perangkat Pembelajaran Materi Vektor Berbasis Pembelajaran Elektronik - Niken Yuniarti; I Nyoman Sudana Degeng; Nurmida Catherine Sitompul (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2020)
Nowadays, the development of science and technology have been rapidly developed, including education. To produce learning tools, namely the Learning Implementation Plan (RPP) , learning materials, Student Worksheets (LKS), and vector quiz materials based on E-Learning for students of Class X MIPA are the objectives of this study. This product is designed to provide wider opportunities for students without having to limit the time (hours) of learning in class. The development of learning tools in this study is based on the theory of the development of the 4-D, namely; defining. design; development, and dissemination, which in this study the dissemination stage was not carried out. It is necessary to adjust the Learning Implementation Plan (RPP) on vector material based on e-learning for students of Class X MIPA